Implementasi ISAK 35 Sebagai Standar Penyusunan Laporan Keuangan pada Madrasah Diniyah Ula dan Wustho Baiturrahman Kumbang Jangkar Situbondo - Yanto, Roni; Herfiah, Rifa; Nisa’, Khoirun (Jurnal Ilmiah Raflesia Akuntansi, 2024)
The aim of this research was to identify the results of implementing financial reports based on ISAK 35 in non-formal religious education public organizations, namely Madrasah Diniyah Ula and Wustho Baiturrahman Kumbang Anchor Situbondo. This research used a descriptive qualitative method with data collection techniques through observation, interviews and documentation at Madrasah Diniyah Ula and Wustho Baiturrahman Kumbang Anchor Situbondo. The conclusion of this research was that the financial report form of Madrasah Diniyah Ula and Wustho Baiturrahman Kumbangsari still uses a simple method, namely only in the form of recording cash inflows and cash outflows and including descriptions of transactions that had occurred, not yet implementing the applicable financial reporting guidelines, namely ISAK 35 which included Comprehensive Income Report, Cash Flow Report, Net Asset Change Report, Financial Position Report (Balance Sheet), and Notes to Financial Reports (CaLK).